Vaginal mesh surgery is efficient to treat pelvic organ prolapse grade 3 in elderly women - O. S. Korotkevich; V. G. Mozes; I. A. Eizenakh; A. V. Soloviev; V. V. Vlasova (Фундаментальная и клиническая медицина, 2019)
Aim. To evaluate the surgical treatment of pelvic organ prolapse grade 3 in elderly women.Materials and Methods. We consecutively recruited 86 elderly women (60 to 75 years old) suffering from pelvic organ prolapse grade 3. Out of them, 56 patients underwent vaginal mesh surgery while 30 refused surgical treatment. After 1 year, we assessed stress urinary incontinence using a cough test and Valsalva maneuver. Pain intensity was measured using the Numeric Rating Scale whereas quality of life was assessed by Pelvic Floor Disability Index (PDFI-20). The primary outcome measure was the prevalence of pelvic organ prolapse symptoms while the secondary outcome measure was the frequency of stress urinary incontinence and low quality of life upon 1 year of follow-up.Results. After 1 year of follow-up, patients who received a surgical treatment were characterized by a statistically significant decrease in both frequency and intensity of complaints and symptoms of pelvic organ prolapse. Pelvic Organ Prolapse Distress Inventory score was 8.3 (4.2-12.5) and 79.2 (79.2-100) in patients with or without surgical treatment respectively. Similar results were showed using Colorectal-Anal Distress Inventory score (6.2 (3.1-6.2) and 68.8 (62.5-71.9) and Urinary Distress Inventory score (8.3 (4.2-8.3) and 83.3 (79.2-87.5), in treated and untreated individuals, respectively. Total Pelvic Floor Disability Index score was 22.8 (11.5-27.0) in women who underwent a vaginal mesh surgery and 227.2 (226.1251.0) in those who did not. All indicated differences were statistically significant.Conclusions. Vaginal mesh surgery is efficient for the treatment of pelvic organ prolapse grade 3 in elderly women.